(untitled) (Stato, Chiese e pluralismo confessionale, 2025)
In an increasingly unstable world with record-setting high levels of conflicts, displacement, environmental change and inequalities, religious and other minorities run the risk of being demonised and scapegoated. Portrayed as threats, of being disloyal to the State or of ‘not assimilating sufficiently, religious and other minorities run the risk of being ‘otherised’ in the rising rhetoric of nationalistic populism used by political actors in an increasing number of regions of the world - and denied their basic rights to equality without any discrimination.